Implementation of a New Web-Based Student Admission Information System at Smp Pelita Nusantara Using the Rapid Application Development (Rad) Method - Dian Aditya; Edy Widodo; Asep Arwan Sulaeman (PT FORMOSA CENDEKIA GLOBAL, 2024)
The process of accepting new learners in schools often faces challenges in terms of effectiveness and efficiency. This study aims to overcome this problem by implementing a new student admission information system using the Rapid Application Development (RAD) method. The RAD method is used because of its flexibility in rapid and iterative system development. In this study, a web-based information system was developed to facilitate prospective students and schools in the registration process. This system allows prospective students to register online from anywhere. This study also aims to minimize data input errors and optimize the registration process time. The results showed that the implementation of a new student admission information system using the RAD method can increase the effectiveness and efficiency of the admission process in schools.